Non-invasive Analyses of Packaged Food Using Time-Domain NMR Relaxometry - Almeida, L.S.; Kock, F.V.C.; Barbosa, L.L.; Colnago, L.A. (Springer, 2026)
This overview explores time-domain nuclear magnetic resonance (TD-NMR) relaxometry as a rapid, non-invasive analytical tool for evaluating packaged food products. While traditional invasive methods are often laborious and time-consuming, TD-NMR harnesses the radio-frequency transparency of most packaging materials to enable direct analysis. Furthermore, by utilizing relaxometry and diffusion measurements, this technique provides critical data on fat and water content, compartmentalization, texture, spoilage, and adulteration. In particular, this work outlines the fundamental principles of TD-NMR and highlights its application in dairy, edible oils, sauces, jams, and beverages. Ultimately, as this technology matures for consumer use, TD-NMR stands to significantly enhance food safety, quality, and supply chain transparency by facilitating straightforward, on-site analysis of packaged goods.
Keywords: TD-NMR; Relaxometry; Diffusion; Packaged food; Non-invasive analysis; https://purl.org/pe-repo/ocde/ford#1.04.02